ANALYSIS Of DENSITY, COVERAGE AND BIOMASS Of SEAGRASS Enhalus acoroides IN TRIKORA BEACH Of MALANG RAPAT VILLAGE BINTAN REGENCY RIAU ARCHIPELAGO PROVINCE - Rizal, Muhammad; Amin, Bintal; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Increased concentration of CO2 in the atmosphere caused the increasing average temperature of the earth globally (global warming) that triggered the climate change. Seagrass is one of the marine resources that considerably potential as a sequester of CO2 (blue carbon) in an effort to mitigate global warming. Trikora beach has seagrass community is composed by different types, one of them is Enhalus acoroides which has an important role as a carbon sink. This study was conducted in May 2016 in Trikora Beach, Bintan, which aims to determine differences of density, the percentage of seagrass coverage and differences in biomass based on a seagrass tissue at the above ground (leaves) and below ground (rhizomes and roots) each the station and the relationship between the density towards seagrass biomass. Data obtained using quadrat transect method at 18 points sampling. The results showed that the density of seagrass in the study sites was high, the density of seagrass in Station 2 was higher than Station 1. Reviewed by percentage of seagrass coverage status was classified as poor and the category of moderately with the higher percentage of seagrass coverage in Station 2 than Station 1. The largest value of biomass was found on rhizomes and roots of seagrass at both stations. The seagrass area less under the influence of anthropogenic and physical environment (Station 2) has the potential of biomass is greater than the seagrass area opposite condition (Station 1). Keywords: Global warming, Biomass, Seagrass, Trikora beach.